Uplink Null-Space Expansion for Multiuser Massive MIMO in Time-Varying Channels Under Unknown Interference - Kabuto Arai; Kazuki Maruta; Chang-Jun Ahn (IEEE Access, 2020)
This article proposes a novel postcoding design scheme for suppressing inter-user interference (IUI) and inter-cell interference (ICI) in uplink multiuser massive multiple-input multiple-output (MIMO) system in time-varying channel environments. In the uplink system, the base station (BS) designs postcoding weight based on estimated channel state information (CSI) to suppress IUI. When user terminals move, the estimated CSI is outdated because actual channels vary with time. This causes IUI and leads to degrading the system capacity. Besides, ICI extensively arises in multiuser massive MIMO systems since many users are simultaneously supported in each cell. The accuracy of CSI estimates is degraded since ICI contaminates the uplink pilot sequences from desired users. Adopting a weight design based on minimum mean square error (MMSE) criteria, we can suppress ICI adequately, and exploiting plentiful degrees of freedom (DoFs) of massive array, we can also suppress IUI even in time-varying channels by steering many nulls for one user based on null-space expansion (NSE) scheme. The computer simulations clarify that the proposed scheme has superior SINR performance in Rayleigh fading channel at low speed, low SIR, and high SNR regions while it is effective at almost all conditions in Rician fading channel.